Pengaruh Penggunaan Smartphone Terhadap Motivasi Belajar Siswa Sekolah Dasar di Kecamatan Mapanget, Kota Manado - Kosmas Sobon (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
The aim of this research is to explain influence smartphone on learning motivation of elementary school students Mapanget Subdistrict Manado City. This research is in four elementary schools used sample are 84 students. This research is a quantitative study used the survey’s method with the following stages: observation of the location of the research, preparation of questionnaires, distribution of questionnaires, validity testing, data collection, processing of research results, analysis of the results of research, and discussion. The result showed that the effect of smartphone on the learning motivation of students in elementary school Mapanget Subdistrict was 0.057 or 5.7% with a significance  0.028 < 0,05. The results of testing t-table is greater than t count, namely t-hitung = 2.232 ≥ (t-tab) = 1.989. This means that smartphone have an effect on students’ learning motivation even though it is in the low category 5.7%. It is recomended that students do not use excessive smartphones both at school and at home. Parents and teachers need to supervise children in using smartphone everday  because the effect  of smartphone on students’ learning motivation is very low.